A Novel Antimicrobial Peptides From Pine Needles of Pinus densiflora Sieb. et Zucc. Against Foodborne Bacteria - Lee, Junho; Kang, Hee Kyoung; Cheong, Hyeonsook; Park, Yoonkyung (Frontiers in Microbiology, 2021)
Pine needles are used in several East Asian countries as food or traditional medicine. It contains functional components that exhibit a wide spectrum of pharmacological effects such as antioxidant, antimicrobial, anti-diabetic, and anti-inflammatory activities. We determined and characterized the novel antimicrobial peptides (AMPs) isolated from Pinus densiflora Sieb. et Zucc. The four active pine-needle (PN) peptides showed antimicrobial activity against foodborne bacteria with minimum inhibitory concentration (MIC) values within the range of 8–128 μg/ml. PN peptides showed no detectable hemolytic activity or cytotoxicity at the antimicrobial concentrations. The N-terminal amino acid sequence of the PN5 was identified using Edman degradation and Antimicrobial Peptide Database (APD) homology analysis showed that it was not identical to any other plant peptide. This suggests that PN5 can serve as an alternative therapeutic agent to be used in the food industry.